Antibiotic consumption and healthcare-associated infections in a tertiary hospital in Belgrade, Serbia from 2011 to 2016 - Perić, Aneta; Dragojević-Simić, Viktorija; Milenković, Bojana; Vezmar Kovačević, Sandra; Šuljagić, Vesna (The Journal of Infection in Developing Countries, 2018)
Introduction: Healthcare-associated infections (HAIs) and irrational use of antibiotics in healthcare settings are major global public health concerns. Surveillance of HAIs in intensive care units (ICU), surgical-site infections (SSIs), and Clostridium difficile infections (CDIs), together with implementation of antibiotic stewardship, are cornerstones of hospital infection prevention programs. The aim of this study was to evaluate antibiotic consumption, especially of broad spectrum antibiotics, in relation to HAI incidence density (ID). Methodology: The study was conducted from 2011 to 2016 in a tertiary hospital, the Military Medical Academy (MMA), in Belgrade, Serbia. Through regular hospital surveillance we identified all patients with a new HAI. Data on consumption of antibacterials for systemic use were expressed as defined daily dose per 100 bed days (DDD/100 BD). Results: The highest incidence density (ID) of HAI was observed among patients in surgical ICUs (47.2 per 1000 patient-days), while the highest incidence rate among SSI was 3.7%. Moreover, the highest ID of CDI in medical patients was 6.2 per 10,000 patient-days, while in surgical patients it was 4.3 per 10,000 patient-days. The most frequently used antibiotics were cephalosporins, aminoglycosides and carbapenems (16.0 ± 2.3, 4.8 ± 0.7, 4.3 ± 0.7 DDD/100 BD, respectively). There was no significant correlation between consumption of any groups of antibiotics and ID of CDI in medical and surgical patients. Conclusion: The multidisciplinary healthcare team would have crucial importance in the implementation of the antibiotic stewardship program in order to decrease unnecessary exposures of patients treated in healthcare settings.